Customer Satisfaction Modelling of The Indonesia Sharia Bank (BSI) - Basrowi Basrowi; Johary Haji Ali; Tulus Suyanto (International Journal of Science and Applied Science: Conference Series, 2022)
The purpose of this study is to analyze the effect of service quality on customer satisfaction of Indonesian Islamic banks (BSI), analyze the effect of product innovation on BSI customer satisfaction, and analyze the simultaneous effect of service quality and product innovation on BSI customer satisfaction. The research design used correlational quantitative research. Data were collected using a survey method to customers of Indonesian Islamic banks as many as 175 customers who have been customers for at least 1 year. The research location is in the Special Capital Region of Jakarta. To increase the validity and reliability of the data, in-depth structured interviews with BSI customers were also used. Based on the results of the study, it can be concluded that, there is a significant effect between service quality on BSI customer satisfaction, there is a significant effect between product innovation on BSI customer satisfaction, and there is a simultaneous influence between service quality and product innovation on BSI customer satisfaction. The implication of this research is that when Indonesian Islamic banks want to increase customer satisfaction, the aspects that need to be improved are improving product innovation then increasing service quality.